2016
DOI: 10.1007/s10995-016-2114-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Outcomes for Hispanic Women with Gestational Diabetes Using the Centering Pregnancy© Group Prenatal Care Model

Abstract: Objective To determine the impact of Centering Pregnancy-based group prenatal care for Hispanic gravid diabetics on pregnancy outcomes and postpartum follow-up care compared to those receiving traditional prenatal care. Methods A cohort study was performed including 460 women diagnosed with gestational diabetes mellitus (GDM) who received traditional or Centering Pregnancy prenatal care. The primary outcome measured was completion of postpartum glucose tolerance testing. Secondary outcomes included postpartum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 16 publications
4
51
0
Order By: Relevance
“…24 This might also explain the present finding that those who were born in the USA had higher resilience scores than those born outside of the USA, even though the difference was not statistically significant. Lastly, one-third of the present study population was enrolled in group-based prenatal care, and although there was no significant difference in resilience scores between those in group-based care and those in traditional prenatal care, a growing body of evidence indicates that group-based prenatal care offers social support among women at risk of adverse perinatal outcomes, 25 In conclusion, the present findings contribute to the understanding of resilience in pregnancy and have important clinical and research implications. First, the study investigated the use of an easy-toimplement, validated tool, the CD-RISC 25, to assess resilience; this tool could be readily incorporated into existing prenatal health and mental health assessments.…”
Section: Risk Factormentioning
confidence: 79%
See 1 more Smart Citation
“…24 This might also explain the present finding that those who were born in the USA had higher resilience scores than those born outside of the USA, even though the difference was not statistically significant. Lastly, one-third of the present study population was enrolled in group-based prenatal care, and although there was no significant difference in resilience scores between those in group-based care and those in traditional prenatal care, a growing body of evidence indicates that group-based prenatal care offers social support among women at risk of adverse perinatal outcomes, 25 In conclusion, the present findings contribute to the understanding of resilience in pregnancy and have important clinical and research implications. First, the study investigated the use of an easy-toimplement, validated tool, the CD-RISC 25, to assess resilience; this tool could be readily incorporated into existing prenatal health and mental health assessments.…”
Section: Risk Factormentioning
confidence: 79%
“…This might also explain the present finding that those who were born in the USA had higher resilience scores than those born outside of the USA, even though the difference was not statistically significant. Lastly, one-third of the present study population was enrolled in group-based prenatal care, and although there was no significant difference in resilience scores between those in group-based care and those in traditional prenatal care, a growing body of evidence indicates that group-based prenatal care offers social support among women at risk of adverse perinatal outcomes [25], and resilience should be further explored in group-based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reviewed favorable outcomes using a similar adaptation of CenteringPregnancy in a population of Spanish‐speaking women diagnosed with gestational diabetes . The authors described a compressed 4‐session schedule of groups with individuals enrolling in the late second or early third trimester of pregnancy, following a diagnosis of gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The group ANC model can be especially useful for women with chronic conditions. A recent study has shown that women with GDM participating in group ANC are more likely than those receiving traditional ANC to complete postpartum glucose tolerance testing, have a higher rate of breastfeeding initiation, and higher rates of exclusive breastfeeding at their postpartum visit …”
Section: Translating Paradigms Into Interventionsmentioning
confidence: 99%
“…A recent study has shown that women with GDM participating in group ANC are more likely than those receiving traditional ANC to complete postpartum glucose tolerance testing, have a higher rate of breastfeeding initiation, and higher rates of exclusive breastfeeding at their postpartum visit. 33 The biggest challenge, perhaps, will be to strengthen primary care services to ensure that women have continuous access to high-quality care services to address their health needs across the lifespan. 34 In LMICs, however, some of these general medical services may be overcrowded, and focused on an older demographic.…”
Section: Health Systems Responsementioning
confidence: 99%